MEMAHAMI ISLAM LOKAL MELALUI KITAB SERIBU MASAIL: STUDI KOMPARASI TEKS ARAB-MELAYU - Lutfiyah Alindah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
The  spread  and  development  of  Islam  in  the  Indonesia  not  only  brought Islam together, but also brought Islamic culture in the form of literature. The development  in teaching Islamiccultural  tradition  is  important  in  the process of Islamization.  Many  books  were  translated,  composed  or  adapted  to  many languages in the archipelago. The books are compiled in what is known as sastra kitab  (literature  of  Islamic  theology).  Its  two  versions,  the  Masail  Sayyidi 'Abdullah bin Salam  lin Nabi  in  the Arabic version or  Seribu Masail  in Malay version,  are  still  preserved.  Both  of  these  texts  are  part  of  the  process  of translation  from  Arabic  texts  into  Malay  text  which  have  variations  either  in structure  linguistic  or meaning.This  paper  examines  the  variations  occurring  in process of translation between Arabic text and Malay text, and how the variations are manifested  in  these  two  texts. This  research  is  important because  it  looks at Sirah nabawiyah (history of  the prophet)  that documents both written and verbal teachings  of  Islam.  In  addition,  this  study  contains  the  theological  values  and dialogue between Muslims and non-Muslims. By using George Steiners  theory, this study tries to examine the difficulties and the paradoxes created by translation from  one  language  to  another.This  study  demonstrates  that  the  final  translation between MasÄil  Sayyidi  ˜AbdullÄh  Bin  SalÄm  li-NabÄ«  text  and  Seribu Masa'il have variations both in the structure of linguistics and meanings.